Effectiveness of Patient Rights Education Program on Knowledge among Nurses in a Selected Hospital at Mangalore - Halder, Smita; M., Nalini; Shetty, Sukesh (Journal of Health and Allied Sciences NU, 2024)
Background Patient rights are basic rules of conduct between patients, medical care providers, and the institutions and the people supporting them. Patient Right Education program provides an opportunity to improve nurses knowledge about patient rights. It fosters communication between patients and nurses, which helps achieve patient satisfaction and reduce the number of violations cases of patient's rights in the hospital. This study aims to find the effectiveness of patient rights education programs among nurses.Materials and Methods A quasiexperimental approach and one group pretest posttest design were adopted for this study. One hundred subjects were selected through a convenient sampling technique in the selected tertiary Hospital, Mangaluru, Karnataka, India. A pretest was conducted on the first day using a structured knowledge questionnaire, and the patient rights education program was conducted for the participants on the same day. The posttest was conducted on the 7th day after the education program.Results Among 100 nurses, the posttest knowledge score (9.67 + 1.67) regarding patients' rights was more than the pretest knowledge (7.43 + 1.67) score. The paired t-test showed that the calculated p-value was 19.381, more than the tab value of 1.98. Hence, it was found that the program effectively improved the knowledge by showing the difference in mean knowledge score at a 5% significance level. For item-wise comparison, McNemar's test was used, and there was an improvement in 50% of patient rights items.Conclusion This study concluded that nurses need a proper awareness system about patient rights for nurses in hospital settings.
Keywords: hospital; education program; nurses; patient rights; satisfaction